Prevalence and Risk Factors of Urinary Incontinence in Frail Elderly Females - Walaa W. Aly; Hala S. Sweed; Nora A. Mossad; Mohammad F. Tolba (Journal of Aging Research)
Background/Purpose. Urinary incontinence (UI) is an important geriatric health problem, and it is linked to frailty syndrome. We had conducted a study to detect the prevalence and risk factors of UI and its effect on quality of life (QOL) among frail elderly females living in Cairo, Egypt. Methods. We carried out a cross-sectional study on 130 frail elderly females sixty years and older, attending Ain Shams Geriatrics Hospital, Cairo, Egypt. Each patient gave oral consent and then was subjected to history taking, full clinical examination, diagnosis of frailty (clinical frailty scale), assessment of UI by the Arabic version of International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF), assessment of QOL by using the Arabic version of Incontinence Impact Questionnaire Short Form (IIQ-7 SF), and complete urine analysis. Results. The prevalence of UI among the studied population was 80%. Mixed UI was the most prevalent type. UI was significantly associated with older age, functional impairment, multiparity, osteoarthritis, stroke, vaginal prolapse, and laxative use. All IIQ-7 subscales were higher (worse health-related QOL) for women with mixed UI. Conclusion. Urinary incontinence is prevalent in frail elderly females. Mixed UI, compared with other types, has a significant negative impact on all domains of quality of life.